Morphine administration during low ovarian hormone stage results in transient over expression of fear memories in females - Perez-Torres, Emily M.; Ramos-Ortolaza, Dinah L.; Morales, Roberto; Santini, Edwin; Rios-Ruiz, Efrain J.; Torres-Reveron, Annelyn (Frontiers in Behavioral Neuroscience, 2015)
Acute exposure to morphine after a traumatic event reduces trauma related symptoms in humans and conditioned fear expression in male rats. We aimed to determine whether acute administration of morphine alters consolidation of fear learning and extinction. Male and female rats in proestrus and metaestrus (high and low ovarian hormones respectively) underwent fear conditioning and received saline or morphine (2.5 mg/kg s.c.). The next day they underwent extinction. Results showed increased freezing during extinction only in the morphine metaestrus group while morphine did not affect males or proestrus females. Recall of extinction was similar on all groups. On a second experiment, a subset of rats conditioned during metaestrus was administered morphine prior to extinction producing no effects. We then measured mu opioid receptor (MOR) expression in the amygdala and periaqueductal gray (PAG) at the end of extinction (day 2). In males and proestrus females, morphine caused an increase in MOR in the amygdala but no in the PAG. In metaestrus females, morphine did not change MOR expression in either structure. These data suggests that ovarian hormones may interact with MORs in the amygdala to transiently alter memory consolidation. Morphine given after trauma to females with low ovarian hormones might increase the recall of fear responses, making recovery harder.